Scottish education in the twentieth century - Paterson, Lindsay (Edinburgh : Edinburgh University Press, 2003)
Scotland's education system has been claimed by many to be one of the most successful in the world and its alleged decline in recent decades has generated a great deal of controversy. This book is the first full history of twentieth-century Scottish education.
1. Introduction -- 2. Expansion and Democracy -- pt. I. Competition and Opportunity, 1880s-1930s -- 3. Elementary Education -- 4. Post-Elementary Education -- 5. University Education -- 6. Technical and Adult Education -- pt. II. Welfare and Individualism, 1940s-1990s -- 7. Primary Education -- 8. Secondary Education -- 9. Higher Education -- 10. Further and Community Education -- 11. Conclusions.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Education -- Scotland -- History -- 20th century; Éducation -- Écosse -- Histoire -- 20e siècle.; EDUCATION -- General; Education; Scotland; Erziehung; Schottland; 1900-1999; History